MORPHOLOGICAL AND SYNTACTICAL ERRORS IN ENGLISH ESSAYS WRITTEN BY EFL STUDENTS - Ni Ketut Pertiwi Anggraeni (Universitas Indraprasta PGRI, 2018)
This research aims at showing morphological and syntactical errors in English Department students’ essays. Besides, this research also focuses on seeking factors affecting the errors, which include interlanguage error and intralanguage error. The data of this research were 30 English essays written by English Department students in Jakarta. The data was analyzed using error analysis to describe syntactical and morphological errors found in students’ essays and the factors affecting the errors. The results show that the most dominant errors were inflectional errors (120 or 66%) in morphological level and tenses errors (52 or 41%) at the syntactical level. The analysis also revealed that there were 93 or 79% intralanguage errors in morphological level and 102 or 81% intralanguage errors in the syntactical level. These findings imply that the teacher of English as a foreign language (EFL) should be aware of errors made by the students and the cause of errors in writing.Keywords: writing; EFL; morphology; syntax; error analysis.